Pengaruh Pendapatan Bagi Hasil dan Pemberian Bonus terhadap Loyalitas Nasabah di Bank Syariah Mandiri Kantor Cabang Sangatta - K Khairi; Eko Nursalim; P Parno (International Journal Ihya' 'Ulum al-Din, 2018)
This type of research is descriptive quantitative. This study uses analytical techniques that include path analysis with the aim to find out the direct and indirect influence of independent variables on the dependent variables processing data using SPSS, simultaneous testing (F test) and individual testing (t test). The population in this study are customers in Bank Syariah Mandiri Sangatta Branch Office. And the number of samples taken by 98 respondents by using random sampling technique. The results showed that there is a significant influence between income sharing (X1) and bonus (X2) to customer loyalty (Y) either partially or simultaneously. From the results if the data is known value of correlation coefficient (R) of 0,542 with interpretation between 0,40 - 0,599 which means existence of positive relation between variable of revenue sharing and giving bonus to customer loyalty, and included in category strong enough. The results of this study indicate that the revenue-sharing variable and bonus giving contributes to customer loyalty variables with a total influence of 29.4% and the remaining 70.6% is likely determined by other factors and not examined in this study. And the path equation is Y = 0,366X1 + 0,297X2.